48 THE SILENCING MEDIATOR OF RETINOID AND THYROID HORMONE RECEPTORS REPRESSES ADIPOGENESIS VIA ITS DISTAL INTERACTING DOMAIN. (1st March 2006) - Yu, C.; Sutanto, M. M.; Cohen, R. N.
Abstract : Obesity is known to be a risk factor for the development of type 2 diabetes mellitus and the metabolic syndrome. Thus, it is important to understand the factors that modulate adipogenesis. Adipogenesis requires the nuclear hormone receptor (NHR) peroxisome proliferator-activated receptor gamma (PPARgamma). NHRs recruit coactivators (CoAs) in the presence of agonists to increase gene transcription; in addition, some NHRs also recruit nuclear receptor corepressors (CoRs) under certain circumstances. CoRs, such as the nuclear corepressor protein (NCoR) and the silencing mediator of retinoid and thyroid hormone receptors (SMRT), recruit a histone deacetylase complex to repress gene transcription. Using a RNA interference system to decrease SMRT and NCoR expression in 3T3-L1 cells, we have previously shown that CoRs repress adipogenesis and decrease the expression of adipocyte-specific proteins by modulating PPARgamma transcriptional activity. We have additionally shown that the intracellular balance of CoRs and CoAs dictates the ability of thiazolidinediones (TZDs), which are PPARgamma ligands used clinically in the treatment of diabetes mellitus, to stimulate adipocyte differentiation. To define the mechanisms of CoR recruitment by PPARgamma in 3T3-L1 cells, we have now focused on the corepressor SMRT. SMRT contains two interacting domains (IDs) that are required for interactions with NHRs. Interestingly, and contrary to other NHRs, PPARgamma interacts with SMRT specifically via the SMRT C-terminal ID (SMRT ID1). To define the amino acids important in specifying the ability of ID1 to function, residues within this domain were mutated to the corresponding residues in the proximal SMRT ID (ID2). Interestingly, a single amino acid within ID1, which is not conserved in ID2, appears to be vital in the recruitment of SMRT by PPARgamma. In contrast, this specific sequence is not required for SMRT interactions with the retinoic acid receptor (RAR), another NHR that interacts strongly with SMRT. Thus, the ability of PPARgamma to recruit the corepressor SMRT is dependent on specific residues within the SMRT C-terminal ID that are distinct from amino acids important for interactions with other NHRs. We have shown that the ability of TZDs to up-regulate PPARgamma-mediated processes is dependent on the balance of CoRs and CoAs. These data also suggest that it might be possible to specifically alter PPARgamma-SMRT interactions to modify TZD action on adipogenesis.